FOREIGN WORKING WOMEN FORM SUB-SAHARAN AFRICA IN SPAIN. CHALLENGES FOR SOCIAL INTERVENTION - Peterson, Maame Aboagyewaa; Estrada, Irene; Palma García, María de la Olas (Interacción y Perspectiva, 2021)
The South of the European continent is constituted as a gateway for migration, Spain being one of the countries of the union with the highest rates of forced migration. The social integration of immigrants becomes more effective if the strategy of addressing their socio-economic characteristics and migratory life experiences is assumed. This study shows the importance of focusing professional social intervention for migrants on their socio-demographic characteristics and their life experiences-in order to achieve their integration in a comprehensive and personalized way. The objective of this research is to know the sociodemographic characteristics of immigrant women and the relevance these characteristics have on the support they receive. This is to demonstrate the importance of personalizing interventions for the social integration of the group under study through the profession of social work. It is carried out from a qualitative approach through in-depth interviews with three social work professionals and six women of African origin. The results show that, in order to achieve the integration of the group, it is essential to start from the need to personalize the intervention for each person; with the social work professional being the reference expert. It concludes with the need for renewal in the intervention and adaptation of the intervention depending on the personal life, cultural, social, economic and educational background, demographic and other characteristics of each migrant.